The SARS-CoV-2 Coronavirus and the COVID-19 Outbreak - Lauxmann, Martin Alexander (2020)
Fil: Fil: Lauxmann, Martin Alexander. Brandenburg Medical School Theodor Fontane, Brandenburg an der Havel, Germany